Latinos’ diminished returns of educational attainment on reducing food insecurity: the role of ethnic disparities in family structure and employment - Assari, Shervin (Frontiers in Public Health, 2024)
Background Higher education is widely recognized as a strategy to mitigate food insecurity. However, marginalized and racialized groups, especially Latinos, often do not experience the same economic and health benefits from their educational achievements as non-Latino Whites, highlighting a pattern of diminished returns within these communities. Aims This study aims to explore the disparities in how educational attainment influences marital status and employment, and subsequently, food insecurity among Latino and non-Latino adults. Methods Utilizing data from the 2022 National Health Interview Survey (NHIS), which encompassed 27,648 adults from both Latino and non-Latino backgrounds, this research applied a structural equation model to examine the relationship between educational attainment, ethnicity, and food insecurity. The study specifically focused on the mediating roles of marital status and employment. Results Findings reveal significant interactions between education and ethnicity affecting marital status and employment, both of which serve as protective factors against food insecurity. These results indicate that higher levels of unemployment and lower marriage rates may disproportionately escalate food insecurity among Latinos, irrespective of educational attainment. Conclusion The study highlights profound societal and environmental obstacles that prevent Latinos from leveraging educational achievements to improve their marital and employment statuses, and thereby, their food security. Addressing these disparities demands targeted interventions directed at Latino communities to bridge gaps in employment and marriage rates stemming from educational disparities. A holistic strategy that transcends mere access to education is essential to dismantle the societal barriers that undermine the educational dividends for Latino communities.